Kaidah Al-Su'āl wa Al-Jawāb dalam Al-Qur'an: Analisis Pola Pertanyaan dan Jawaban sebagai Pendekatan Kebahasaan dalam Tafsir - Chaerul Umam Shabran; Halimah Basri; Amir Hamzah (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
This study examines the principle of al-Su'āl wa al-Jawāb (question and answer) as one of the linguistic principles in Qur'anic interpretation. This principle plays a significant role in understanding the relationship between questions and answers found in Qur'anic verses, thereby enabling a more accurate comprehension of the messages conveyed by the Qur'an. The study aims to explain the concept of al-Su'āl wa al-Jawāb, its interpretive principles, and the various patterns of questions and answers found in the Qur'an. This research employs a qualitative approach using library research as its primary method. The findings reveal that the question-and-answer patterns in the Qur'an do not always conform to ordinary human communication. In some verses, the answers directly correspond to the questions posed, whereas in others, the answers may be broader, more specific, more general, or even indirectly address the questions in order to direct attention to matters of greater significance. Furthermore, the relationship between questions and answers may occur within the same verse, within the same chapter (sūrah), or across different chapters of the Qur'an. Therefore, the principle of al-Su'āl wa al-Jawāb plays a significant role in assisting Qur'anic exegetes (mufassirūn) in understanding the meanings, purposes, and messages of the Qur'an in a more comprehensive manner.